Emergency embolization for the treatment of acute hemorrhage from intercostal arteries - Stampfl, Ulrike; Sommer, Christof-Matthias; Bellemann, Nadine; Kortes, Nikolas; Gnutzmann, Daniel; Mokry, Theresa; Gockner, Theresa; Schmitz, Anne; Ott, Katja; Kauczor, Hans-Ulrich; Radeleff, Boris (Emergency radiology, 2014)
To evaluate embolotherapy for the emergency management of acute bleeding from intercostal arteries. Between October 2003 and August 2012, 19 consecutive patients with hemorrhage from intercostal arteries were scheduled for emergency embolization. The primary study endpoints were technical and clinical success, which were defined as angiographic cessation of bleeding, and cessation of clinical signs of hemorrhage. The secondary study endpoints were periprocedural complications and 30-day mortality rate. In most patients (74 %), hemorrhage was caused by iatrogenic procedures with subsequent intercostal artery laceration. One of the patients was treated twice for recurrent hemothorax caused by a new intercostal artery pseudoaneurysm 7.5 years after the initial procedure. Thus, 20 procedures were performed in these 19 patients. Overall technical success was 85 %. In six patients, no embolization of the “backdoor” was feasible, and in two of these patients additional embolization of other intercostal arteries was necessary to prevent hemorrhage via collateral vessels. Clinical signs of hemorrhage ceased after embolotherapy in 16 of 20 procedures (clinical success 80 %). The mean follow-up was 358.7 ± 637.1 days. One minor procedure-related complication occurred. The 30-day mortality rate was 21 %, however, this was unrelated to intercostal artery hemorrhage. Embolotherapy is an effective emergency therapy for patients with acute hemorrhage from intercostal arteries. Especially if embolization of the backdoor is not feasible, collateral supply via other intercostal arteries should be either ruled out or embolized to prevent ongoing hemorrhage. Despite successful embolotherapy, a majority of patients underwent surgery during follow-up to remove the symptomatic hematoma.
Gesehen am 02.11.2020